A New Potent and Selective Monoamine Oxidase‐B Inhibitor with Extended Conjugation in a Chalcone Framework: 1‐[4‐(Morpholin‐4‐yl)phenyl]‐5‐phenylpenta‐2, 4‐dien‐1‐one. (15th July 2020) - Maliyakkal, Naseer; Eom, Bo Hyun; Heo, Jeong Hyun; Abdullah Almoyad, Mohammad Ali; Thomas Parambi, Della Grace; Gambacorta, Nicola; Nicolotti, Orazio; Beeran, Asmy Appadath; Kim, Hoon; Mathew, Bijo
Abstract: The general blueprint for the design of monoamine oxidase‐B (MAO‐B) inhibitors has been based on two phenyl or heteronuclei linked via a spacer of appropriate length. In this study, 1‐[4‐(morpholin‐4‐yl)phenyl]‐5‐phenylpenta‐2, 4‐dien‐1‐one (MO10) was prepared by the condensation of 4′‐morpholinoacetophenone and cinnamaldehyde in basic alcoholic medium. MO10 was assessed for inhibitory activity against two human MAO isoforms, MAO‐A and MAO‐B. Interestingly, MO10 showed a remarkable inhibition against MAO‐B with an IC50 value of 0.044 μM along with a selectivity index of 366.13. The IC50 value was better than that of lazabemide (IC50 value of 0.063 μM), which was used as a reference. Kinetics studies revealed that MO10 acted as a competitive inhibitor of MAO‐B, with a K i value of 0.0080 μM. The observation of recovery of MAO‐B inhibition, compared to reference levels showed MO10 to be a reversible inhibitor. MTT assays showed that MO10 was nontoxic to normal VERO cells with an IC50 value of 195.44 μg/mL. SwissADME predicted that MO10 provided advantageous pharmacokinetics profiles for developing agents acting on the central nervous system, that is, high passive human gastrointestinal absorption and blood–brain barrier permeability. Molecular docking simulations showed that MO10 properly entered the aromatic cage formed by Y435, Y398, and FAD of the active site of MAO‐B. On the basis of these results, MO10 can be considered a promising starting compound in development of agents for the treatment of various neurodegenerative disorders. Abstract : Selecting selectivity : 1‐[4‐(Morpholin‐4‐yl)phenyl]‐5‐phenylpenta‐2, 4‐dien‐1‐one (MO10) was prepared and investigated for its monoamine oxidase inhibitory activities. MO10 showed remarkable inhibition against MAO‐B with an IC50 value of 0.044 μM along with a selectivity index of 366.13. Kinetics studies revealed that MO10 acted as a competitive inhibitor for MAO‐B. MTT assays showed that MO10 was nontoxic to normal VERO cells.